Is It Possible to Speak English Without Thinking American? On Globalization and the Determinants of Cultural Assimilation - Alberto Chong (Inter-American Development Bank, Research Department, 2006)
Based on research in linguistics and psychology I use language speech as a reflection of acculturation. I use individual and city-level data from the Lake Ontario area in Canada and study the determinants of cultural assimilation. I focus on education, age, income, and in particular, on some variables typically discussed when globalization issues come up, such as immigration, television viewing, borders, and residence history of the individuals. I find that actual contact does matter as a determinant of cultural homogenization. Virtual contact appears to be irrelevant. This finding is robust to changes in specification and to different empirical methods.
Keywords: 330; Sprache; Globalisierung; Kulturelle Identität; Kanada